Segmented filamentous bacteria‐induced immune responses: a balancing act between host protection and autoimmunity. Issue 4 (13th June 2018) - Flannigan, Kyle L.; Denning, Timothy L.
Summary: Segmented filamentous bacteria (SFB) are Gram‐positive, spore‐forming, bacteria that primarily colonize the ileum of the small intestine. Upon direct adherence to intestinal epithelial cells, SFB actively stimulate innate and adaptive immune cell activation. The cardinal features of SFB‐induced gut immunity – T helper type 17 (Th17) cell differentiation, IgA production and barrier protection – lead to the containment of SFB and further afford protection against invading pathogens. Th17 cells and interleukin‐17A, however, can also reach peripheral sites and exacerbate autoimmunity. In this review, we highlight salient characteristics of SFB–host interactions and detail the cellular and molecular immune mechanisms involved in coordinating these responses. Abstract : In this review, we highlight salient characteristics of segmented filamentous bacteria–host interactions and detail the cellular and molecular immune mechanisms involved in coordinating these responses.